Menentukan Nilai Premi Tunggal Bersih Asuransi Jiwa Seumur Hidup Menggunakan TMI IV Tahun 2019 dengan Variasi Uang Pertanggungan (UP) - Diah Ayu Lestari; Kasih Simbolon; Septi Melani Putri Tambunan (Lembaga Pengembangan Kinerja Dosen, 2024)
Life insurance is an agreement made by the insurance company as the party responsible for providing the guarantee in the form of providing money as risk compensation if an event occurs, such as the death of an insurance participant. As compensation, the insurance participant has the obligation to pay a certain amount of premium to the insurance company. Single premium is a premium payment method that is made once at the beginning. Single premium is a way of paying insurance premiums that are paid all at once at the beginning. Sum Insured is funds that will be given the insurance company to the heirs as a replacement if the insurance participant dies. The purpose of this research is to determine the premium value and compare the premium value if various sums insured are given. And it was found that the greater the sum insured, the greater the premium value that must be paid, and the older a person is when taking out life insurance, the greater the premium value that must be paid.